Effect of milk replacer on kid performance among small holder farmers (Asian Journal of Medical and Biological Research, 2016)
An experiment was conducted with 15 Black Bengal kids of both sexes (in 3 groups) were fed two different milk replacer using ingredient shotti (T1), skim milk (T2) and no milk replacer- kids with mother, termed as control group (T0) at Southern agro trade, Subarnachar, Noakhali. The average total DM intake and milk dry matter intake were not significantly differed among the treatment group. Total dry matter intake was not affected by intake of liquid milk replacer or goat milk. The CP intake were ranged from 19.97 to 20.93 g/d. Total CP intake was not significantly differed among the group but T1 group was slightly higher(0.42 g/d) than T0 and T2. The amount of protein intake (g/d) was followed NRC (1985) recommendation. DMI from concentrate (g/d), DMI from green grass (g/d) and DMI from percent live weight were not significantly differed among the treatment groups. The average daily gain was not significantly (P>0.05) differed among the treatment group. The average growth rate (57.42 61.20 g/d) of all kid of Black Begal goat was lower than the Angora goats (115.00-125.00 g/d) and Alpine goats (153.00-258.00 g/d). Dry matter (DM) digestibility (%) was significantly (p